The Contemporary Irish Historical Novel, 2000-2016 - Batista, Camila Franco (ABEI Journal, 2017)
My research aims at building a study of the contemporary Irish historical novel, contemplating works published between 2000 and 2016. The corpus consists of novels by celebrated authors such as Joseph O’Connor, Sebastian Barry, Nuala O’Connor, Jamie O’Neill, Mary Morrissy, and Lia Mills. The study aims at demostrating that contemporary novels have moved away from the Walter Scott’s model, representing not only past national struggles but also transnational historical relations between Ireland and the United States. This article will discuss how contemporary Irish historical novels intertwine the past and the present by critically examining past and contemporary social, political, cultural, and literary issues, such as gender, social and racial discrimination, and emigration.